2000
DOI: 10.1093/carcin/21.4.607
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer, heterocyclic aromatic amines from meat and N-acetyltransferase 2 genotype

Abstract: Breast cancer risk has been hypothesized to increase with exposure to heterocyclic aromatic amines (HAAs) formed from cooking meat at high temperature. HAAs require enzymatic activation to bind to DNA and initiate carcinogenesis. N-acetyltransferase 2 (NAT2) enzyme activity may play a role, its rate determined by a polymorphic gene. We examined the effect of NAT2 genetic polymorphisms on breast cancer risk from exposure to meat by cooking method, doneness and estimated HAA [2-amino-1-methyl-6-phenylimidazole[4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
4
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 51 publications
7
65
4
3
Order By: Relevance
“…Not only the quantity of red meat intake is of interest but also the cooking of it. Associations between the consumption of fried, grilled, barbecued or pan-fried red meat and the risk of colon cancer (Schiffman & Felton, 1990), colorectal adenomas , breast cancer (Zheng et al, 1999) and stomach cancer (Ward et al, 1997) were found, but there are several investigations that were not able to detect any association (Delfino et al, 2000;Gertig et al, 1999;Ambrosone et al, 1998). In the present study, the preparation of red meat shows a great variability across the participating countries and regions.…”
Section: Discussionmentioning
confidence: 49%
“…Not only the quantity of red meat intake is of interest but also the cooking of it. Associations between the consumption of fried, grilled, barbecued or pan-fried red meat and the risk of colon cancer (Schiffman & Felton, 1990), colorectal adenomas , breast cancer (Zheng et al, 1999) and stomach cancer (Ward et al, 1997) were found, but there are several investigations that were not able to detect any association (Delfino et al, 2000;Gertig et al, 1999;Ambrosone et al, 1998). In the present study, the preparation of red meat shows a great variability across the participating countries and regions.…”
Section: Discussionmentioning
confidence: 49%
“…Previous studies have tended to find inverse relationships with consumption of poultry (Delfino et al, 2000;Ronco et al, 2003) and have generally been statistically non-significant. Our findings do not provide strong evidence of an association with poultry intake and breast cancer in either pre-or postmenopausal women.…”
Section: Discussionmentioning
confidence: 90%
“…Due to differences in enzyme activity, polymorphisms in genes of metabolizing enzymes may increase breast cancer risk in women who are exposed to carcinogens from meat intake. Results on meat consumption, metabolic polymorphisms and their role in breast cancer are conflicting [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%